Curcumin: A Natural Pan-HDAC Inhibitor in Cancer - Soflaei, Sara S.; Momtazi-Borojeni, Amir Abbas; Majeed, Muhammed; Derosa, Giuseppe; Maffioli, Pamela; Sahebkar, Amirhossein (Current Pharmaceutical Design, 2018)
Background: Histone deacetylases (HDACs) are a group of histone modification enzymes with pivotal role in disease pathogenesis especially in cancer development. Increased activity of certain types of HDACs and positive effects of HDAC inhibition has been shown in several types of cancers. Furthermore, few HDAC inhibitors have been approved by the FDA for cancer treatment, and this has generated interest in finding new HDAC inhibitors as potential anti-cancer agents. Curcumin, a natural polyphenol extracted from turmeric, is a safe and bioactive phytochemical with a wide range of molecular targets and pharmacological activities including promising anti-cancer properties. Methods: A systematic literature search using appropriate keywords was made to identify articles reporting the modulatory effect of curcumin on HDACs in different types of cancer in vitro and in vivo. Results: HDACs have emerged as novel targets of curcumin that their modulation may contribute to the putative anti-cancer effects of curcumin. Curcumin inhibits HDAC activity, and down-regulates the expression of HDAC types 1, 2, 3, 4, 5, 6, 8 and 11 in different cancer cell lines and mice, while the activity and expression of HDAC2 have been reported to be up-regulated by curcumin in COPD and heart failure models. Conclusion: Available in vitro and in vivo data are encouraging and in favor of the HDAC inhibitory activity of curcumin but clinical evidence on the efficacy of curcumin as an adjunct treatment in cancer patients is lacking.
Keywords: tumor